Digital Transformation of Learning Media in Elementary Schools: A Shift from Physical Props to Augmented Reality - Gunawan Gunawan; Ni Made Yeni Suranti; Imran Imran; Lovy Herayanti; Kurniawan Arizona; Fahmi Yahya (Indonesian Journal of Elementary and Childhood Education, 2025)
The transformation of learning media in elementary schools has undergone a significant evolution, moving from a reliance on physical props to the utilization of immersive technologies. This review article aims to analyze this paradigm shift, starting from the use of static visual media to the adoption of Augmented Reality (AR). Through a literature review of various recent studies, the analysis focuses on how interactive digital platforms and gamification act as a transitional bridge before reaching the stage of AR technology, which is capable of visualizing abstract concepts in real-time. The analysis reveals that the shift to AR does not only replace the role of physical props in terms of cost and space efficiency but also provides a superior impact on enhancing student engagement, reducing cognitive load, and fostering deeper conceptual understanding. This review concludes that digital transformation in elementary schools is a crucial step in creating an adaptive and futuristic learning environment for Generation Alpha.